Network church : a Pentecostal ecclesiology shaped by mission - Lord, Andrew. (Global Pentecostal and Charismatic Studies, 2012)
Pentecostal churches have grown over the last century but only a limited amount has been written about their ecclesiology. Much of the existing work focuses on congregational models and contemporary practice. This book argues the need for a pentecostal systematic approach to ecclesiology. Utilising the method of Amos Yong a pentecostal ecclesiology based on a network church structure is developed. Systematic issues of catholicity are addressed through mission insights on partnership, and a hospitable approach to contextualisation is developed. This book, therefore, suggests new ways forward in pentecostal studies and ecclesiology.